2017
DOI: 10.1148/radiol.2016161233
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Source Single-Energy Multidetector CT Used to Obtain Multiple Radiation Exposure Levels within the Same Patient: Phantom Development and Clinical Validation

Abstract: Purpose:To develop, in a phantom environment, a method to obtain multidetector computed tomographic (CT) data sets at multiple radiation exposure levels within the same patient and to validate its use for potential dose reduction by using different image reconstruction algorithms for the detection of liver metastases. Materials andMethods:The American College of Radiology CT accreditation phantom was scanned by using a dual-source multidetector CT platform. By adjusting the radiation output of each tube, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…However, when CT is performed with considerably reduced doses, diagnostic performance deteriorates for clinical tasks involving low contrast resolution (eg, brain CT, hepatic CT, and pancreatic CT), even if image noise and contrast-to-noise ratio are maintained or improved with IR algorithms (73). The maximum dose reduction potential and imaging texture (IR-related artifacts, such as a pixelated or plastic appearance) differ according to the IR algorithm used (74,75), and there has been controversy over how much the radiation dose can be reduced with each IR algorithm without loss of low contrast detectability (76,77). However, the decision whether to increase the radiation dose substantially to depict subtle lesions in most children, who may have more conspicuous lesions or no lesions at all, should be carefully considered, according to each clinical condition.…”
Section: Deterioration Of Low Contrast Detectability At Low-dose Settmentioning
confidence: 99%
“…However, when CT is performed with considerably reduced doses, diagnostic performance deteriorates for clinical tasks involving low contrast resolution (eg, brain CT, hepatic CT, and pancreatic CT), even if image noise and contrast-to-noise ratio are maintained or improved with IR algorithms (73). The maximum dose reduction potential and imaging texture (IR-related artifacts, such as a pixelated or plastic appearance) differ according to the IR algorithm used (74,75), and there has been controversy over how much the radiation dose can be reduced with each IR algorithm without loss of low contrast detectability (76,77). However, the decision whether to increase the radiation dose substantially to depict subtle lesions in most children, who may have more conspicuous lesions or no lesions at all, should be carefully considered, according to each clinical condition.…”
Section: Deterioration Of Low Contrast Detectability At Low-dose Settmentioning
confidence: 99%
“…This allows for the assessment of radiation-dose thresholds in regards to diagnostic yield in a clinical setting while not exposing patients to additional radiation. Additional CT examinations for research purposes have been reported, and the ethical considerations were discussed [ 22 , 23 ]. A recent study reported a technique to reconstruct multiple dose levels from a dual-energy CT examination [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional CT examinations for research purposes have been reported, and the ethical considerations were discussed [ 22 , 23 ]. A recent study reported a technique to reconstruct multiple dose levels from a dual-energy CT examination [ 23 ]. However, even in this study, an additional CT examination with a not-clinically indicated radiation exposure for the patients was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the S3 level on the basis of our clinical experiences and studies, which indicated that higher IR strength results in a pixelated, blotchy, plastic image appearance (i.e. IR-specific artefacts) and S3 is the preferable setting to obtain well-balanced image quality between appearance and diagnostic performance for reduced dose abdominal CT. [34][35][36] The slice thickness and interval were both 5 mm for all images.…”
Section: Image Reconstructionmentioning
confidence: 99%